Meningococcal disease: Epidemiological Characteristics of the Municipal Hospital Souza Aguiar in Rio de Janeiro/RJ, Brazil between 2010-2014 - Fernando Pessuti; Dina Soriano; Bruno Boechat Maciel (Universidade de Santa Cruz do Sul, 2016)
Background and Objectives: Meningococcal disease (MD) is a major worldwide concern in public health. In the state and city of Rio de Janeiro, MD has key relevance, having historically been the source of several outbreaks and epidemics. Methods: This was a retrospective longitudinal study that analyzed the epidemiological characteristics of hospitalizations for MD at Hospital Municipal Souza Aguiar (HMSA) based on three variables: gender, age, reason for discharge or evolution in the period from January 2010 to April 2014. Results: There were 121 admissions for MD in HMSA, predominantly children under the age of four years, which represented 53.7% (n = 65), whereas individuals aged younger than fifteen years accounted for 80.1% of admissions (n = 97). During the study period 65 males and 56 females were hospitalized. Regarding the reason for discharge or evolution of hospitalized patients, there was a predominance of the classification "discharge after improvement" throughout the study period, corresponding to approximately 67% (n = 81) of all hospital discharges, oscillating between 77.8% in 2013 and 48.7% in 2010. Conclusion: These numerical data represent the profile of patients diagnosed with MD in HMSA, so it can help the surveillance system of the city of Rio de Janeiro aiming to intervene more specifically with both prevention of cases and deaths due to meningococcal infections.